A sociologia e os problemas de nosso tempo: circulação de fake news em tempos de pandemia - Batista, Antônio Renato Salgado (2023)
This work had as its object of research the fake news that circulated about the Coronavirus pandemic in social media between the years 2020 and 2022 and how was the perception of students from a high school about this problem over the period. It presents, as an integral part of this dissertation text, a didactic material that proposed in its body a contextualization and historicization of the information age as a structural element of our time, a bibliographical review of the specialized literature in the problems of digital communication, with emphasis on fake news, accompanied by a content analysis as an analytical and procedural framework whose lens proved to be very useful for teaching and learning the subject in Sociology classes, especially in the context of this type of media in Brazil during the pandemic years. In this way, the work sought to point out possibilities to approach the problem in the school environment with the scientificity and pedagogical and social responsibility that it requires in the face of the risks that society offers.